Past and recent glacier fluctuations in Kanchenjunga Himal, Nepal - Asahi, Katsuhiko; Wataoabe, Teiji (Journal of Nepal Geological Society, 2000)
Kanchenjunga Himal, which lies in the easternmost part of the Nepal Himalaya, is a typical area under strong summer monsoon environment. Studies on glacial variations of Kanchenjunga Himal can reveal climate changes particularly monsoon fluctuations since the Last Glaciation and those in the recent time. The aerial photo interpretation and field observation identified changing valley morphology from an ambiguous U-shaped to a V-shaped along the Ghunsa Khola at an altitude of approximately 2.800 m. This clear morphological change may indicate the former maximum extent of the glaciers. Geographical positions of glacial landforms and relative dating data led to the classification of the glacial activities into at least five stages. From the younger lo older order, they are historical stage (around the early part of the Twentieth Century), the Little Ice Age, the Holocene, and the late and early substages of the Last Glaciation. The two substages could be correlated with the Last Glacial Maximum (LGM) and Marine Isotope Stage 3 or 4. The extent of the glaciers in the LGM was not generally so large as compared with that of the existing glaciers. Relatively small glacier expansion can probably suggest, weaker summer monsoon and less precipitation in the LGM period. A comparison of the 1992 glaciers with those of 1958 in the Ghunsa Khola drainage, the main drainage of Kanchenjunga Himal, revealed that out of examined 57 glaciers, 50% of them had retreated in the period from 1958 to 1992. Also, 38%of the glaciers were under stationary conditions, and 12% were advancing. Consequently, the general tendency should be regarded as "mostly retreating". The distribution and magnitude of the glacier variations suggest that general rising of air temperature possibly caused the recent glacier retreat, and that the stationary or advancing conditions were likely to be related to the local increase and variations of precipitation.